Aluno-Pesquisador: desenvolvendo a pesquisa no ensino fundamental - Arenhaldt, Rafael; Fagundes da Silva, Cássio; da Silva Felippe, Leonardo; Luis Machado, José (Revista da Extensão, 2024)
Aluno-Pesquisador: desenvolvendo a pesquisa no ensino fundamental